Strategic business models: opportunities for business model innovation in the automotive industry - in-depth analysis of car subscriptions in Germany - Carioba, Marco Antonio Müller (2022)
Digitization and changing customer preferences have an impact on the determinants of sales and ownership in the automotive industry. In this context it is crucial to understand the new, disruptive business models and their potential for market players. The purpose of this report is to analyze the distinct characteristics of different business models that exist in the automotive industry in Germany today, and to provide an in-depth analysis of the business model components for car subscriptions. The report also provides an evaluation of the advantages and vulnerabilities of the given business model and offers an outlook for future research on the topic.